A Collaborative Approach to Providing Best-Practice Childhood Feeding Guidance - Freedman, Marjorie R.; Gogol, Sally J. (International Journal of Child Health and Nutrition, 2013)
Objective: To examine whether training on Division of Responsibility, provided to members of a childhood feeding collaborative, increased familiarity, knowledge, and confidence in disseminating information to parents of young children. Methods: Training was provided to 47 public health nurses and 22 breastfeeding task force members. A within-group pretest, posttest, follow-up design assessed changes in familiarity, knowledge and confidence. Results: Amongst public health nurses, training resulted in a significant increase in familiarity (P < .001); knowledge that restricting amount of food provided to overweight infants and/or children is inappropriate (P < .05); and that children need frequent exposure to new foods (P < .05). Confidence in disseminating information also significantly increased (P < .001). Conclusions and Implications: Health care providers who counsel parents about childhood feeding practices should be trained to increase familiarity with, knowledge of, and confidence in disseminating best practice feeding guidelines to help ensure provision of consistent, accurate messaging.